A STYDY OF GUEST'S EXPECTATION AND PERCEPTION OF HOTEL SERVICE QUALITY: CASE OF KHAJURAHO, INDIA - Saurabh Kumar Dixit (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2013)
Evaluation of customers’ perception and satisfaction of service quality is widely acknowledged as being a favourable strategy in the hotel industry. In recent years, the hotels in India have encountered difficult times due to the increasing customer demands, and due to the strong internal industry competition development. However, the hospitality industry’s main concern around the globe is to cater for its customer needs and their desires, which are mostly addressed through personal services. Present research paper aims to provide an assessment of service quality suggested by Grönroos (1982; 1990) by empirically examining hotel guests’ perception of process quality and outcome quality; and the relationships between the perceived service quality, customer satisfaction in the hotel industry of the study area.Therefore, the hotel businesses that are able to provide quality services to its ever demanding customers in a warm and efficient manner, are those businesses which will be more likely to obtain a long term competitive advantage over their rivals. However, since the hotels are offering intangible and perishable personal service encounters, managing these services in terms of offering quality experience to their guests, it must be of a paramount concern of any hotel business, and the way which personalized services are provided. The present paper will highlight the behavior of the hotel guests from hospitality products and services in the study area. The study will be helpful in identification of GAP’s in service delivery process and measures adopted to bridge those GAP’s.